2016
DOI: 10.1007/s11307-016-0973-6
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of Radiomic Features in [11C]Choline and [18F]FDG PET/CT Imaging of Nasopharyngeal Carcinoma: Impact of Segmentation and Discretization

Abstract: Discretization generated larger effects on features than segmentation in both tracers. Features extracted from [C]choline were more robust than [F]FDG for segmentation. Discretization had very similar effects on features extracted from both tracers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
105
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(110 citation statements)
references
References 53 publications
3
105
1
1
Order By: Relevance
“…quantization, [51][52][53] SUV discretization, 54 pre-processing steps 55 and the choice of respiration-averaged CT for attenuation correction. 56,57 The impact of tumour delineation on textural features computation was also assessed in PET images.…”
Section: Positron Emission Tomography Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…quantization, [51][52][53] SUV discretization, 54 pre-processing steps 55 and the choice of respiration-averaged CT for attenuation correction. 56,57 The impact of tumour delineation on textural features computation was also assessed in PET images.…”
Section: Positron Emission Tomography Imagesmentioning
confidence: 99%
“…56,57 The impact of tumour delineation on textural features computation was also assessed in PET images. [50][51][52]55 Finally, an attempt of interpreting PET textural indices was carried out in a very recent work, where heterogeneity quantified by texture analysis was investigated on simulated patient data. 58 Here, the authors found that homogeneity, entropy, short-run emphasis and long-run emphasis were sensitive to the presence of uptake heterogeneity, whereas high grey-level zone emphasis and low grey-level zone emphasis were mostly sensitive to the average uptake.…”
Section: Positron Emission Tomography Imagesmentioning
confidence: 99%
“…By calculating how frequently pairs of pixels with specific values in specific spatial relationships occur throughout the ROI, descriptors such as energy, entropy, and correlation were computed . Studies that have investigated the robustness of GLCM features over varying region segmentations and bin sizes for discretization also found that GLCM features demonstrate high robustness …”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first series that studied many parameters (31 textural indices) in such a large cohort of HNSCC (284 patients). Comparing results should take into account the methodological choices underlying indices calculation . In a series of 9 HN and cervical cancers, El Naqa et al showed the prognostic interest of Contrast textural index using both manual contouring and fixed threshold (40% of SUV max ).…”
Section: Discussionmentioning
confidence: 99%
“…Comparing results should take into account the methodological choices underlying indices calculation. 32,33 In a series of 9 HN and cervical cancers, El Naqa et al 34 showed the prognostic interest of Contrast textural index using both manual contouring and fixed threshold (40% of SUV max ). Moreover, Cheng et al 21,22 studied the prognostic value of 22 textural indices with different segmentation methods (fixed SUV >2.5 and 42% of SUV max and relative thresholds) in 88 patients with locally advanced oropharynx cancers.…”
Section: Discussionmentioning
confidence: 99%